MAKNA BUDAYA DALAM PENDIDIKAN - Eva Iryani (Jurnal Ilmiah Universitas Batanghari Jambi, 2014)
Education and culture have a very close relationship, education without culture will be nothing, and culture without education will make the culture itself die. Education is as medium for the transmision of the culture from generation to generation. Culture also gives contribution for education to create intellectual human being and having a good manner. The local culture and national have a very high value in educational process.Key words : Education, Culture, intellectual generation.